Analisis Politik Hukum Dan Implementasinya - Islamiyati Islamiyati; Dewi Hendrawati (Faculty of Law, Diponegoro University, 2019)
The relationship between politics and law is very familiar, the law is a legislation that is actually a crystallization of political wills that interact and influence each other. Political law is defined as the official line of state policy to create and enact legislation in order to achieve the goals and goals of the state as contained in the preamble of the Constitution of 1945 Alenia IV. Implementation of legal politics in the form of legislation that is used as a tool to achieve state goals, in accordance with the national legal framework of national law, which can be seen in PROLEGNAS AND PROLEGDA.Keyword: law, politics, implementation. ABSTRAKHubungan antara politik dan hukum sangat akrab, hukum merupakan peraturan perundang-undangan yang sebenarnya adalah kristalisasi dari kehendak-kehendak politik yang saling berinteraksi dan saling mempengaruhi. Politik hukum diartikan sebagai garis resmi kebijakan negara untuk membuat dan menetapkan peraturan perundang-undangan guna mencapai cita-cita dan tujuan negara seperti yang terdapat pada pembukaan UUD NRI 1945 alenia IV. Implementasi politik hukum berupa ditetapkannya perundang-undangan yang digunakan sebagai alat untuk mencapai tujuan negara, yang sesuai dengan kerangka dasar politik hukum nasional, yang dapat dilihat di PROLEGNAS DAN PROLEGDA.